Hadith #15 - The Forty Hadith Qudsi - Abu Hurayrah (The Forty Hadith Qudsi)
On the authority of Abu Hurayrah (may Allah be pleased with him), who said that the Prophet (ﷺ) said: Allah the Almighty said: I am as My servant thinks I am (1). I am with him when he makes mention of Me. If he makes mention of Me to himself, I make mention of him to Myself; and if he makes mention of Me in an assembly, I make mention of him in an assembly better than it. And if he draws near to Me an arm’s length, I draw near to him a cubit, and if he draws near to Me a cubit, I draw near
Grade: Sahih